Yaacov Deutsch. Judaism in Christian Eyes: Ethnographic Descriptions of Jews and Judaism in Early Modern Europe, trans. by Avi Aronsky - Kaplan, Debra (Studies in Christian-Jewish Relations, 2013)
No abstract is available.